The Mediating Role of Knowledge Management Processes in the Relationship Between Digital Transformation and Intellectual Capital in the Service Sector - Asad Ardda; Hashem Osamah Yahya Mohammed; Khairil Faizal Khairi (Simo Excel PLT, 2025)
Indexed Publicaton (Tier 2)